Fase dan Tugas Perkembangan Sosio-emosional Anak Sekolah Dasar - Dinda Ayu Yunitasari; Adhy Putri Rilianti (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2023)
The aim of this research is to determine the phases and factors that influence children's socio-emotional development tasks at the age of 6-11 years. This research is a type of literature study research where the sources of information in this research are obtained from various sources such as books, journals and relevant articles. The results of this research show that socio-emotional development is an important aspect in child development. Several factors influence the development of children's socio-emotional tasks at this age, including social interaction, adaptation, compliance with social norms, maturation and learning experiences and relationships with adults around the child. This needs to be considered because social and emotional intelligence is a key element in children's development, including the ability to recognize other people's feelings, interact well, manage emotions and motivate oneself. These are important aspects that help children overcome their developmental tasks and shape their character.